Urine fertilizer for vegetable production - a case study in Nepal and Ghana. - Pradhan, S.; Amoah, Philip; Piya, R. C.; Heinonen-Tanski, H. (2012)
Eco-toilets (human urine and faecal matter collected separately) are one of the best ways to solve sanitation problem, and this practice also improves the environment and increases the food production. This study focuses on experimental demonstration of use of urine, wood ash and poultry droppings (PD) as a fertilizer in central Nepal and in Accra, Ghana. In Nepal, Fertilizer value of urine+ash was compared with animal manure and no-fertilization in the cultivation of radish, potato, broadleaf mustard, auliflower and cabbage. The urine + ash or manure fertilized plots received 54 kgN/ha for radish, 51 kgN/ha for potato, 81 kgN/ha for broadleaf mustard and 77 kgN/ha for cabbage and cauliflower. Similarly in Ghana, urine was compared no fertilization and urine + PD (poultry dropping) was compared with NPK (mineral ertilizer)+PD as a dose of 121 kgN/ha. In Nepal, the urine+ash fertilizer produced significantly (P<0.05) higher broadleaf ustard biomass than obtained from animal manure and without fertilization. It was demonstrated that urine+ash can produce higher yields than manure fertilizer, the differences being >24 t/ha radish tuber, >95 kg/ha potato tuber, >19 t/ha cauliflower total biomass and >15 t/ha cabbage total biomass. In Ghana, urine produced 1.2 ton/ha more cabbage head biomass compared to no fertilization and urine+PD produced 0.82 t/ha more cabbage head biomass compared to NPK+PD. Furthermore, in Nepal, N-fertilizer value of 4 litres urine is equal to the 1 kg of dry manure and in Ghana N-fertilizer value of 2 litres of urine is equal to 1 kg of poultry droppings. In conclusion, human urine can be used as fertilizer alone or combined with wood ash and poultry droppings and this can produce similar or even more vegetable biomass than can be achieved with no fertilization, manure fertilization or NPK+PD.